PROFIL FARMAKOKINETIKA RADIOFARMAKA ETAMBUTOL BERTANDA TEKNESIUM-99m SEBAGAI SEDIAAN SIDIK TUBERKULOSIS - Wangsaatmadja, Hanafiah; Kartini, Nanny (Jurnal Farmasi Indonesia, 2011)
The invention of Ethambutol labeled technetium-99m as a radiopharmaceutical for early detection of Mycobacterium tuberculosis gave a significant role in managing of pulmonary as well as extra pulmonary tuberculosis diseases. The clinical studies indicated that the application of this diagnostic agent was very specific and very accurate to determine not only for pulmonary TB infection, but also the existing of TB in abdomen, head, bone, and even in the fingertips. Physicochemical characteristics of this agent have been reported by the previous researcher; however the pharmacodynamic and pharmacokinetic studies as a parameter required in order to fulfill of good manufacturing practice is still necessary to be investigated.Â  In this study, the observation of pharmacokinetic profile in animal through the organ bio-distribution, blood kinetic, and renal clearance/urinary excretion have been carried out. The maximum blood concentration (46%) of 99mTc-Ethambutol was found less than 5 minutes after intra venous injection, and decreased by 0.04% in the next 24 hours. From the kinetic data interpretation, the biological half life of 99mTc-Ethambutol was found out around 0.26 hours for the distribution time and 3.19 hours for the elimination. Â  ABSTRAK Penemuan Etambutol bertanda teknesium-99m sebagai sediaan radiofarmasi untuk mendeteksi secara dini keberadaan Mycobacterium tuberculosis, menjadi penting artinya bagi program penatalaksanaan penyakit TBC paru dan non-paru. Uji coba klinis, telah menunjukkan bahwa penggunaan sediaan diagnostik ini spesifik dan sangat akurat dalam menentukan tidak hanya infeksi tuberkulosis (TB) paru, tetapi juga TB yang terdapat di daerah abdomen, kepala, tulang, bahkan di ujung jari sekalipun. Karakteristik fisiko-kimia sediaan ini telah dilaporkan oleh peneliti terdahulu, namun demikian, kajian farmakodinamika dan farmakokinetika sebagai parameter yang disyaratkan dalam rangka penyediaan obat yang baik masih perlu diteliti. Dalam penelitian ini telah dilakukan pengamatan profil farmakokinetika pada hewan percobaan melalui uji biodistribusi, studi kinetika darah, dan ekskresi uriner. Kadar maksimum (sekitar 46%) radiofarmaka 99mTc-Etambutol dalam darah hewan uji ditemukan kurang dari 5 menit setelah penyuntikan intra-vena, dan menurun hingga 0,04% dalam waktu 24 jam kemudian. Dari interpretasi data kinetika, diperoleh waktu paruh biologis 99mTc-Etambutol sebesar 0,26 jam untuk biodistribusi dan 3,19 jam untuk eliminasi.